2016
DOI: 10.1016/j.seizure.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-imaging evaluation after the first afebrile seizure in children: A retrospective observational study

Abstract: Children below the age of two demonstrated significantly higher percentages of abnormal imaging (59%), as did children presenting with status epilepticus (58%). Neuro-imaging should be considered in infants and those with focal or prolonged seizures. Neuro-imaging informed decision making in 6-8% of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 12 publications
4
29
1
1
Order By: Relevance
“…Several factors identified in available aforementioned studies include persistent postictal focal neurologic deficit, failure to return to baseline within several hours after the seizure, presence of predisposing conditions, focal seizure, multiple seizures, status epilepticus, and 2 years or younger at presentation. 2,[4][5][6][7][8] Seizure duration of at least 5 minutes and unknown seizure duration at the time of presentation are the only factors that had significant positive correlation with use of head CT in our cohort. There was no increased use of head CT for younger age, multiple seizures, focal seizure, predisposing factors, or focal neurologic examination findings as noted in other studies.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Several factors identified in available aforementioned studies include persistent postictal focal neurologic deficit, failure to return to baseline within several hours after the seizure, presence of predisposing conditions, focal seizure, multiple seizures, status epilepticus, and 2 years or younger at presentation. 2,[4][5][6][7][8] Seizure duration of at least 5 minutes and unknown seizure duration at the time of presentation are the only factors that had significant positive correlation with use of head CT in our cohort. There was no increased use of head CT for younger age, multiple seizures, focal seizure, predisposing factors, or focal neurologic examination findings as noted in other studies.…”
Section: Discussionmentioning
confidence: 74%
“…Even in the presence of focal seizures, only persistent Todd paresis and age ≤18 months were predictive of clinically urgent abnormal findings on neuroimaging; absence of secondary generalization and multiple seizures on presentation were not predictive. 4 A recent study by Al-shami et al 8 of neuroimaging in children after first-time afebrile seizure demonstrated that children below the age of 2 years and children presenting with status epilepticus had significantly higher percentage of neuroimaging abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…[5] In our study, MRI abnormalities was seen in 7 (10.7 % ) children which was consistent with the study done by Sharma et al [18] where they found that overall incidence of neuroimaging abnormality was 8%, (26% in high risk children and 2 % in low risk) emphasizing the need of neuroimaging in only high risk category like presence of predisposing conditions and focal seizures in less than 3 years , whereas well appearing and low risk children don't warrant immediate neuroimaging. [18] However , in various studies with children evaluated for first episode of unprovoked seizures prevalence of abnormalities in the neuroimaging ranged from 0-21% [19] probably due to inclusion of non significant MRI findings as well.…”
Section: Issn (0): 2347-3363; Issn (P): 2347-3355mentioning
confidence: 99%
“…Seizure's in children account for 1% of all visits to emergency department [5]. Common causes of seizure in children include cortical malformations such as lissencephaly, focal cortical dysplasia etc., neurocutaneous syndromes like neurofibromatosis type 1, sturge weber syndrome etc, trauma, infections, tumours, metabolic and electrolyte disturbances and mesial temporal sclerosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the seizures are classified as generalized or focal based on how the initial onset is and also on the basis of the description the seizure episode. A first episode may be down to an underlying neurological disease or may as well be initial presentation of epilepsy [5]. Initial workup in pediatric population usually involves an electroencephalograph and a neurosonogram.…”
Section: Introductionmentioning
confidence: 99%